Moenawar Khalil: The Career and Thought of Indonesian Muslim Reformist - Hamim, Toha (Studia Islamika, 1997)
The study of Islamic reform movement in Indonesia in general give less attention to the genuine character is engaged outside the political arena. Various scientific papers, both national and international levels, as if not take place to the figures, although they are thought to have inspired the emergence of various new movement in Indonesian Islam. This happens not because the figures were not known to the public, but rather that the study of Islamic reform is often written and analyzed within the framework of the social-historical, while ignoring the doctrinal renewal. As a result, scientific works have forgotten the main elements of the reform, namely the intellectual insight of religious teachings.DOI: 10.15408/sdi.v4i2.779